Perhitungan Subsidi Bus Trans Metro Pekanbaru Koridor V - grosman, Vallon fansgian; Taufik, Hendra; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Precisely on June 18, 2009 has begun the operation of Bus Rapid Transit (BRT) or Mass Public Transportation Facility (MPTF) and named TRANS METRO PEKANBARU (TMP). TMP bus is expected to be one solution to overcome the problems of transportation in the Metropolitan City. Therefore, it is necessary to analyze include Operational Cost of Vehicle (OCV) and subsidy calculations. The result of OCV analysis for medium TMP buses is Rp.10.275,53. And government subsidies for 2017 is Rp.138.224.350,25.Keywords: Trans Metro Pekanbaru, Corridor V, Operational Cost of Vehicle, Subsidy